Program Bimbingan dan Konseling Berbasis Nilai Karakter Taluba Bagi Siswa SMA di Kota Banjarmasin - Muhammad Eka Prasetia; Rudi Haryadi (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2020)
This study aims to determine the design of Guidance and counseling programs in Taluba-based schools in the development of the character of learners, to find out the Taluba Character Concepts in the Banjar / Swamp Tribe Society, and to determine the validity of the developmental guidance and counseling program model. The design of this study is the design of educational research and development (Educational Research & Development) Research and development in the context of education is the process used to develop and validate educational products. The stages used in this study were only 8 stages out of 10 stages. The subjects of development in this study were all high schools in Banjarmasin, both public and private. The approach in this study uses qualitative and quantitative approaches. The technique for collecting data is to use interview techniques and documentation in the form of a literature review and use the Delphi to validate the model created by researchers as guidance and counseling experts and practitioners. The target of this research output is to become a speaker at national/international seminars and to be published in Sinta's e-ISSN Journal. The results obtained are based on the results of quantitative and qualitative validation tests by 3 experts in BK Science and 3 Practitioners who are BK teachers/school counselors who indeed understand the science of Guidance and counseling, the six validators alike state that the hypothetical model of the BK program is developed based Taluba character values ​​are very good, useful, easy, proper and appropriate to be used as a reference for BK teachers in providing guidance and counseling services that are integrated with local wisdom and the culture of the Banjar tribe community.